2020
DOI: 10.3390/geriatrics5020027
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review Examining Associations between Cardiovascular Conditions and Driving Outcomes among Older Drivers

Abstract: There is a vast literature on stroke as a cardiovascular disease and driving outcomes, however little is known about other cardiovascular conditions and driving. The purpose of this review is to examine the literature for studies assessing the effect of non-stroke, vascular conditions on daily driving, reported crash risk and driving decline in older adult drivers as captured by naturalistic methodologies. A systematic review of Embase, Ovid and Scopus Plus examined articles on driving and vascular conditions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Finally, a recent meta-analysis of 10 studies demonstrated a significant reduction of motor-vehicle crashes in OSAS patients using CPAP masks [148]. Smolensky and colleagues [149] provide a detailed overview of sleep disorders, chronic medical conditions, and their risk for drowsy-driving road crashes.…”
Section: Sleep-related Breathing Disordersmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, a recent meta-analysis of 10 studies demonstrated a significant reduction of motor-vehicle crashes in OSAS patients using CPAP masks [148]. Smolensky and colleagues [149] provide a detailed overview of sleep disorders, chronic medical conditions, and their risk for drowsy-driving road crashes.…”
Section: Sleep-related Breathing Disordersmentioning
confidence: 99%
“…By far the most frequently reported disease is high blood pressure (hypertension), followed by cardiac arrhythmia, cardiac insufficiency (heart failure), coronary artery disease, heart attack, and angina pectoris. All of these diseases have a wide variety of different symptoms that can adversely affect driving ability and road safety [ 150 ].…”
Section: Cardiovascular Diseasesmentioning
confidence: 99%
“…Two prominent assessments are the Trail Making Test Part B (Trails B), a measure of divided attention, and the Useful Field of View® (UFOV), a measure of visual processing speed (i.e., subtest 1), divided attention (i.e., subtest 2), and selective attention (i.e., subtest 3) ( Gentzler & Smither, 2012 ). Numerous systematic reviews show that the Trails B and UFOV are associated with on-road driving performance in older drivers ( Dickerson et al, 2014 ; Duncanson et al, 2018 ; Mathias & Lucas, 2009 ; Seong-Youl et al., 2014 ; Vrkljan et al, 2011 ), as well as drivers with Parkinson's disease ( Classen et al, 2015 ; Crizzle et al, 2012a ), multiple sclerosis ( Fragoso et al, 2016 ; Krasniuk et al, 2019 ), traumatic brain injury ( Egeto et al, 2019 ), stroke ( Babulal et al, 2020 ; Devos et al, 2011 ), MCI ( Hird et al, 2016 ; Withaar et al, 2000 ), and dementia ( Bennett et al, 2016 ; Hird et al, 2016 ; Molnar et al, 2006 ; Rashid et al, 2020 ; Withaar et al., 2000 ). However, only a few studies have examined the predictive ability with associated cut-points of the Trails B and UFOV in predicting pass/fail on-road outcomes in older adults with CI ( Bowers et al, 2013 ; Dobbs & Shergill, 2013 ; Duncanson et al, 2018 ; Papandonatos et al, 2015 ; Roy & Molnar, 2013 ; Stern et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%